Conjoined omphalopagus twins: a casereport - Sheila Yadira Gómez-Murillo; Sara Alejandra Solórzano-Morales; Héctor Macías-Avilés (Instituto Nacional de Pediatría, 2014)
Multiple pregnancies are 3% of the total. The most frequent are dizygotic females, however, a small group of them are of monozygotic conjoined twins in some anatomical area. This attracts the attention of physicians because of the rarity of the condition and the difficulties as well as the ethical dilemmas for their treatment. We report a case of male Siamese omphalopagus. They were separated surgically at seven weeks of age. One of them lived six months.